IMPLEMENTASI MEDIA BATANG NAPIER DALAM PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI SEKOLAH DASAR - Gress Vinessa Simorangkir; Mia Apta Cadra. S; Juita Dalimunthe; Resyarusyda Parandrengi (STKIP Subang, 2026)
ABSTRACT This study aims to describe the implementation of Napier's Bones media in improving mathematics learning outcomes, particularly on multiplication of whole numbers, for third-grade elementary school students. The low mathematics learning outcomes, especially on multiplication, became the main issue underlying this research. A Classroom Action Research (CAR) design with two cycles was conducted at SDN 14/I Sungai Baung, Muara Bulian District, involving 20 third-grade students as research subjects. Data were collected through observation, tests (pre-test and post-test), interviews, and student response questionnaires, then analyzed descriptively both qualitatively and quantitatively. The results show that the implementation of Napier's Bones media significantly improved students' learning outcomes, as evidenced by the increase in average scores and learning completeness percentage from cycle I to cycle II. Napier's Bones converts multiplication problems into addition problems, enabling students to understand multiplication concepts concretely. This study contributes to strengthening the empirical foundation for using manipulative-based teaching aids in elementary school mathematics learning. Keywords: Napier's Bones Media, Learning Outcomes, Mathematics, Multiplication, Elementary School ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan implementasi media Batang Napier dalam meningkatkan hasil belajar matematika, khususnya pada materi perkalian bilangan cacah, bagi siswa kelas III Sekolah Dasar. Rendahnya hasil belajar siswa pada mata pelajaran matematika, terutama materi perkalian, menjadi permasalahan utama yang melatarbelakangi penelitian ini. Jenis penelitian yang digunakan adalah Penelitian Tindakan Kelas (PTK) dengan desain dua siklus yang dilaksanakan di SDN 14/I Sungai Baung, Kecamatan Muara Bulian. Subjek penelitian adalah siswa kelas III yang berjumlah 20 orang. Pengumpulan data dilakukan melalui observasi, tes (pre-test dan post-test), wawancara, dan angket respons siswa. Data dianalisis secara deskriptif kualitatif dan kuantitatif. Hasil penelitian menunjukkan bahwa penerapan media Batang Napier secara signifikan meningkatkan hasil belajar siswa, yang terlihat dari peningkatan nilai rata-rata dan persentase ketuntasan belajar dari siklus I ke siklus II. Penggunaan media Batang Napier mengubah persoalan perkalian menjadi persoalan penjumlahan sehingga memudahkan siswa memahami konsep perkalian secara konkret. Penelitian ini berkontribusi dalam memperkuat landasan empiris penggunaan alat peraga berbasis manipulatif dalam pembelajaran matematika di sekolah dasar. Kata kunci: Media Batang Napier, Hasil Belajar, Matematika, Perkalian, Sekolah Dasar